Recurrent ovarian mixed germ cell tumor with unusual malignant transformation: a case report - Yi-Le Lee; Chiung-Ru Lai; Ming-Shyen Yen (BMC, 2019)
Abstract Background The value of this report is the identification of late recurrence with an extremely unusual combination of malignant transformation. In particular, the retroconversion of immature to mature teratoma as well as a somatic-type malignant transformation were both observed postchemotherapeutically in our case. Case presentation We report the case of a 20-year-old girl who completed fertility-sparing surgery and chemotherapy under the diagnosis of ovarian mixed germ cell tumor (immature teratoma and yolk sac tumor) and experienced subsequent recurrence 4 years after a second debulking surgery with a somatic type malignant transformation (teratoma with melanoma and leiomyosarcoma). Multiple metastases developed after a third debulking surgery, and the patient survived for 18 additional months. Conclusions Recurrent disease after repeated cytoreduction and chemotherapy hints a poor outcome despite a generally excellent long-term survival rate among ovarian germ cell malignancies. It is important for clinicians to distinguish those at risk of poorer outcomes and establish individualized postoperative surveillance. Fertility-compromising surgery may be considered in selected patients.